Motorbike gang network in Yogyakarta: Socio-cultural studies between the relation of moral and religion habituation of local teenagers - Birsyada, Muhammad Iqbal; Kintoko, Kintoko; Mehta, Kunal (Program Pascasarjana Universitas Negeri Yogyakarta, 2021)
The study of the phenomenon of the Motorcycle Gang known as Klithih in Yogyakarta at this time is very important and urgent to conduct in order to find various shifts in moral and religious values experienced by adolescents who are members of the Klithih Gang, especially from the perspective of social and religious studies. Thus, this research is expected to provide a solution, especially for the Yogyakarta local government, to overcome various motorcycle gang behavior models, mostly carried out by the school-age youth community. The differences between the previous study and this study are; First, this research focused on the Motorcycle Gang case in Yogyakarta, which has not been studied much by other researchers. Second, this study used a qualitative approach with a phenomenological framework to get a deeper picture of the motor gang involvement process in social and educational aspects. Third, the research locus was in the city of Yogyakarta. Fourth, this study used a combined theoretical conception of social theory and moral values to analyze the interpretation of the research results. The findings of this study are described as follows. First, the Motorcycle Gang's behavior occurs because of the failure to internalize moral and religious education in the family. Psychological and physical violence that occurs in the families of motorcycle gang perpetrators affects children's brain and psychological development. The condition of the two parents who experienced a divorce (broken home) made the children feel traumatized, so they look for an environment that accepts them outside. Second, the influence of their friendly environment is very dominant in triggering teenagers to join the Motor Gang group. Third, the community's social and religious lack control in preventing activities of Motorcycle Gangs around their places of residence. Fourth, students or alumni who are involved in the Motorcycle Gang network indicated a lack of preventive action from schools. Fifth, the shift in socio-religious values in the Gang Motor community occurred because of an appeal for the Klithih group to get recognition from other Motorcycle Gang groups by showing the level of their mental strength among the Gang members.